(untitled) (Malaysia, 1995)
The FHS's First Symposium on Diseases in Asian Aquaculture was held in Bali, Indonesia in 1990. This peer-reviewed volume contains 55 papers presenting original research or reviews of areas of fish health important to the Asia-Pacific Region.
Keywords: Aquaculture,Shellfish,Fishes,Fishes; Diseases,Diseases,Parasites; Asia,Asia,Asia,Asia